Baseline correlations and prognostic impact of serum monoclonal proteins in follicular lymphoma. (16th November 2020) - Mozas, Pablo; Rivero, Andrea; Rivas‐Delgado, Alfredo; Fabregat, Aleix; Piñeyroa, Juan A.; Correa, Juan G.; Nadeu, Ferran; Oliver, Aina; Bataller, Alex; Giné, Eva; Delgado, Julio; Villamor, Neus; et al.
Summary: The presence of a serum monoclonal component has been associated with poor outcomes in some lymphomas. However, data in follicular lymphoma (FL) are scarce. We studied 311 FL patients diagnosed at a single institution, for whom information on serum immunofixation electrophoresis (sIFE) at diagnosis was available. Baseline characteristics and outcomes were compared between patients with a positive (+sIFE) and a negative sIFE (−sIFE). sIFE was positive in 82 patients (26%). Baseline features were comparable between both groups, except for an older age and higher proportion of elevated β2 ‐microglobulin levels in the +sIFE group. With a median follow‐up of 4.6 years, a +sIFE was associated with a higher risk of early relapse (POD24, 27% vs. 15%, P  = 0·02), shorter progression‐free survival (PFS; 42% vs. 52% at 5 years, P  = 0·008), and shorter overall survival (OS; 59% vs. 77% at 10 years, P  = 0·046). In patients >60 years, a +sIFE was an independent predictor of OS [hazard ratio (HR) = 2·4, 95% confidence interval (CI): 1·2–5·0; P  = 0·02]. Approximately one quarter of patients with FL has a +sIFE at diagnosis, which is a predictor of poor outcome. These findings encourage further investigation of its relationship with B‐cell biology and the tumour microenvironment.